Adesão ao Plano S: A resposta da FCT aos novos desafios - Novais, Joana; Pereira, Filipa; Andrade, Miguel; Mendes Moreira, João (BiblioCanto, 2023)
Pôster apresentado na 14ª Conferência Lusófona de Acesso Aberto (ConfOA).